Direct observation of valley-polarized topological edge states in designer surface plasmon crystals - Xiaoxiao Wu (Nature Portfolio, 2017)
The photonic valley-Hall effect can enable the unidirectional propagation of edge states, but often require covers which shield the states from direct measurement. Here, Wu et al. realize photonic valley-Hall effect using designer surface plasmons, enabling the direct observation of topological states.